Short term outcome of retrograde tibiopedal access in management popliteal and infrapopliteal disease - Ghoneim, Baker; Nasser, Mahmoud; Ali, Mohamed (International Surgery Journal, 2018)
Background: Aim was to evaluate the safety and efficacy of retrograde tibiopedal access after failed antegrade recanalization in patients with femero-popliteal and infrapopliteal occlusions. Methods: This is a retrospective study including patients presenting with critical limb ischemia due to femero-popliteal and infrapopliteal occlusions for whom retrograde transpedal/tibial access was used after failure of antegrade approach at the vascular surgery unit in Kasr Al Aini hospitals in the period from June 2015 to June 2017. Results: The study included 18 patients with a mean age of 64 years and male to female ratio 2.6:1. All patients presented with CLI (Rutherford category 4-6), all lesions were Trans Atlantic Society Consensus (TASC) II D, and Technical success was accomplished in 17 cases (94.4 %). In one case, failure to cross the target lesion via both antegrade and retrograde accesses occurred and the patient was immediately converted to an open surgery (popliteal tibial bypass). Complications included 2 puncture site hematoma that were managed conservatively; no AVF. There was no perioperative mortality. Primary patency was 81.25 % at 6 month. Conclusions: retrograde tibiopedal access is safe and effective technique after failed antegrade recanalization in patients with popliteal and infrapopliteal occlusions.